Testing the geographical dimensions of genetic diversity following range expansion in a North American snake. (29th September 2018) - Cox, Christian L; Stringer, Joel F; Moseley, Matthew A; Chippindale, Paul T; Streicher, Jeffrey W
Abstract: Spatial and demographic expansion can alter patterns of genetic variation and have predictable spatial and temporal consequences. Two-dimensional range expansion should result in genetic variation that is correlated with the geographical axis of expansion. Notably, populations across the range of a geographically widespread species may experience expansion and contraction events asynchronously. We tested for the genetic consequences of range expansion in the flat-headed snake, Tantilla gracilis, which inhabits the North American Great Plains and has few barriers to terrestrial dispersal. We sequenced mitochondrial DNA (mtDNA) and nuclear DNA from across the range of T. gracilis, inferred phylogenies and constructed haplotype networks. We observed multiple geographically circumscribed mtDNA clades that varied greatly in their spatial extent, but little range-wide variation in nuclear DNA. Mitochondrial sequence variation was negatively associated with latitude across their geographical range, the expected pattern of northward expansion. Finally, the three largest mtDNA clades exhibited varying demographic patterns, with only one being consistent with recent expansion. Despite substantial mtDNA cladogenesis, the predicted signature of northern range expansion was still detectable in T. gracilis . Our results bolster the notion that post-Pleistocene range expansion was a dominant force shaping the genetic diversity of vertebrates in central North America.